2021
DOI: 10.1021/acsomega.1c03205
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, Immune Regulation, and Antioxidative Assessment of Yeast-Derived Selenium Nanoparticles in Cyclophosphamide-Induced Rats

Abstract: This article introduces an environmentally friendly and more economical method for preparing red selenium nanoparticles (Se-NPs) with high stability, good biocompatibility, and narrow size using yeast as a bio-reducing agent with high antioxidant, immune regulation, and low toxicity than inorganic and organic Se. The yeast-derived Se-NPs were characterized by scanning electron microscopy, transmission electron microscopy, energy dispersive spectroscopy, Fourier transform infrared spectroscopy, X-ray diffractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 70 publications
3
21
0
Order By: Relevance
“…Wu et al. concluded that Se NPs had great ability to regulate oxidative stress and immunity ( 29 ). Recent studies indicated that Se NPs could also serve as therapeutic agents due to their potential for anti-atherosclerotic effect and alleviating histological damage caused by diabetes ( 30 , 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al. concluded that Se NPs had great ability to regulate oxidative stress and immunity ( 29 ). Recent studies indicated that Se NPs could also serve as therapeutic agents due to their potential for anti-atherosclerotic effect and alleviating histological damage caused by diabetes ( 30 , 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the free radical scavenging activity of the green-synthesized NPs on DPPH radicals increases with the increasing concentration of NPs. By comparing our results with previously reported NPs, it has been observed that green-synthesized NPs showed better results as compared to chemically synthesized NPs (Figure f). The biologically active ZnONPs and AgNPs exhibited strong antioxidant potential that governs antioxidant reactions with higher efficacies.…”
Section: Resultsmentioning
confidence: 97%
“…Despite the extensive accumulation of the SeNPs with a tendency to form aggregates of individual particles, no evidence of cell lysis or the distortion of the outer membrane was observed [ 39 , 40 ]. The particles appeared to have a spherical shape and a diameter of approximately 70–120 nm with an average of 80 nm, which has a uniform shape and good dispersion [ 15 ]. Furthermore, strain Y4 was able to reduce the toxic selenite aerobically with the concomitant generation of the SeNPs in LB at a logarithmic phase, as Figure 6 showed.…”
Section: Resultsmentioning
confidence: 99%
“…SeNPs with controllable physical and chemical properties are highly practical. SeNPs are usually synthesized through physical, chemical, and biological methods [ 9 , 10 , 11 , 14 , 15 ]. Furthermore, Selenium nanoparticles have attracted substantial attention recently owing to their great performance, such as their excellent bioavailability and low toxicity.…”
Section: Introductionmentioning
confidence: 99%